Interprofessional Teamwork Innovation Model (ITIM) to promote communication and patient-centred, coordinated care. Issue 9 (14th February 2018) - Li, Jing; Talari, Preetham; Kelly, Andrew; Latham, Barbara; Dotson, Sherri; Manning, Kim; Thornsberry, Lisa; Swartz, Colleen; Williams, Mark V
Abstract : Background: Despite recommendations and the need to accelerate redesign of delivery models to be team-based and patient-centred, professional silos and cultural and structural barriers that inhibit working together and communicating effectively still predominate in the hospital setting. Aiming to improve team-based rounding, we developed, implemented and evaluated the Interprofessional Teamwork Innovation Model (ITIM). Methods: This quality improvement (QI) study was conducted at an academic medical centre. We followed the system's QI framework, FOCUS-PDSA, with Lean as guiding principles. Primary outcomes included 30-day all-cause same-hospital readmissions and 30-day emergency department (ED) visits. The intervention group consisted of patients receiving care on two hospitalist ITIM teams, and patients receiving care from other hospitalist teams were matched with a control group. Outcomes were assessed using difference-in-difference analysis. Results: Team members reported enhanced communication and overall time savings. In multivariate modelling, patients discharged from hospitalist teams using the ITIM approach were associated with reduced 30-day same-hospital readmissions with an estimated point OR of 0.56 (95% CI 0.34 to 0.92), but there was no impact on 30-day same-hospital ED visits. Difference-in-difference analysis showed that ITIM was not associated with changes in average total direct costs nor average cost per patient day, after adjusting for all other covariates in the models, despite the addition of staff resources in the ITIM model. Conclusion: The ITIM approach facilitates a collaborative environment in which patients and their family caregivers, physicians, nurses, pharmacists, case managers and others work and share in the process of care.